OP0311 Synovial Lipodystrophy Induced by Hypercholesterolemia Aggravates Synovitis in An Experimental Model of Osteoarthritis in Rabbits. (15th July 2016) - Largo, R.; Larranaga-Vera, A.; Perez-Baos, S.; Prieto-Potin, I.; Herrero-Beaumont, G.
Abstract : Background: Metabolic syndrome (MetS) is a risk factor for osteoarthritis (OA). While obesity contribution is well characterized, less known is the effect of each component of this syndrome on its own. Particularly interesting is the role of hypercholesterolemia, given the high incidence of cardiovascular events and atherosclerosis in OA patients. Objectives: To study the effect of hypercholesterolemia without any other component of MetS in the synovial inflammation in knee OA. Methods: 16 New Zeland rabbits were fed with a high fat diet (HFD, 0.5% cholesterol+4% peanut oil). Six weeks later, OA was induced by anterior cruciate ligament transection and partial medial meniscectomy, in 10 of these animals (OA+HFD group), and in 10 regular chow fed rabbits (OA group). 10 healthy rabbits fed with regular chow were simultaneously followed (Control group). Twelve weeks after OA induction, animals were euthanized and SM isolated for histological and molecular biology studies. Results: HFD, OA and OA+HFD animals gain significantly less weight than control rabbits at the end of the study. We did not find significant differences in systolic blood pressure, serum glucose or oral glucose tolerance between the groups. HFD fed rabbits showed higher total serum cholesterol, triglycerides and C-Reactive Protein levels than rabbits fed a normal diet. Synovitis score was increased in HFD and OA rabbits, and particularly in OA+HFD group, with the more severe score. Synovitis in OA+HFD was characterized by a massive infiltration of foam RAM11+ cells, with higher presence of multinucleated foam cells and stromal fibrosis than in OA. A huge decrease in the adipose tissue area (%ATA)t ogether with a marked decrease in the adipocyte size was observed in the SM of OA+HFD in comparison to OA and control animals. Furthermore, perilipin1a synthesis was significantly decreased in OA+HFD in comparison to OA and control rabbits. In comparison to controls, synovial leptin and adiponectin gene expressions were markedly decreased in HFD and OA rabbits, and especially in OA+HFD animals (p<0.01 vs OA), and positively correlated with %ATA in these animals. By contrast, serum leptin was increased in HFD and OA+HFD in comparison to control rabbits. We did not find significant differences in the SM gene expression of the proinflammatory cytokines IL-1β, COX-2 or MCP-1, between OA and OA+HFD animals. However, TNF SM expression was significantly increased in OA+HFD vs. OA, and significantly correlated with the presence of RAM11+ cells in the SM of these rabbits. Conclusions: Our data show that hypercholesterolemia is an aggravating factor for OA synovitis, inducing an increased infiltration of macrophages and the disappearance of adipose tissue in the SM. Hypercholesterolemia induced a profound decrease in the adipocyte content in the OA SM, together with a remarkable increase in synovial TNF expression. HFD induced a decrease in the synovial expression of leptin and adiponectin in OA rabbits. However, high levels of serum leptin, probably due to systemic synthesis such as that derived from the liver were found in HFD fed animals. Our data indicate that synovial adipocytes and dyslipemia could play pivotal roles in OA joint deterioration in patients with MetS, and support the concept that the link between obesity and OA transcends mechanical loading Disclosure of Interest: None declared